Paratextualizing Games Investigations on the Paraphernalia and Peripheries of Play - Beil, Benjamin; Freyermuth, Gundolf S.; Schmidt, Hanns Christian (Bild und Bit. Studien zur digitalen Medienkultur, 2021)
Gaming no longer only takes place as a ›closed interactive experience‹ in front of TV screens, but also as broadcast on streaming platforms or as cultural events in exhibition centers and e-sport arenas. The popularization of new technologies, forms of expression, and online services has had a considerable influence on the academic and journalistic discourse about games. This anthology examines which paratexts gaming cultures have produced - i.e., in which forms and formats and through which channels we talk (and write) about games - as well as the way in which paratexts influence the development of games. How is knowledge about games generated and shaped today and how do boundaries between (popular) criticism, journalism, and scholarship have started to blur? In short: How does the paratext change the text?